The emotion of sadness by the Yemeni poet Abdullah Al-Baradouni: عاطفة الحزن عند الشاعر عبدالله البردوني قراءة أسلوبية في قصيدة (أمي) - Yamni, Salih Ahmed; Fazal Ahad, Dr. Fazlullah (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2021)
This stylistic study deals with the poem of the poet Abdullah Al-Baradouni entitled أمي" (My Mother)" in which he laments his mother, whose separation created in him a deep wound which cannot be healed with the passage of time. And he also collected during his choice of vocabulary a number of words and phrases indicating sadness such as ")my sadness" and "my depression") The same is the case with the structural aspect of sentences which was in line with the sadness which emerged in his breast. He chose for his poem such sounds which carried the meaning of sadness such as nun (صوت النون) which shows sadness, and (صوت الحاء,-H), which suggests expression, This study investigated all those aspects and emphasized Al-Baradouni's outstanding position, having delicate poetic sense, intense emotion, and his other artistic aspects in this research.